Mucopolysaccharidosis Type-II with Pathognomonic Skin Appearance: A Case with Pebbling Sign - Ayşe Hitay İnan; Berna Şeker Yılmaz; Fatma Derya Bulut; Sebile Kılavuz; Deniz Kor; Mehmet Karakaş; Halise Neslihan Önenli Mungan (Galenos Yayinevi, 2021)
Mucopolysaccharidosis type-II (MPS-II) is an X-linked lysosomal storage disorder. Here, we report an 8-year-old boy with pebbling sign in the scapular region, coarse facies, claw hand, diastolic murmur, and hepatomegaly. With decreased iduronate-2-sulfatase activity and hemizygous mutation in the IDS gene, the diagnosis was MPS-II. Pebbling sign is a rare but pathognomonic sign of MPS-II.